Model simulated volume fluxes through the Canadian Arctic Archipelago and Davis Strait: Linking monthly variations to forcing in different seasons. Issue 3 (14th March 2014) - Lu, Youyu; Higginson, Simon; Nudds, Shannon; Prinsenberg, Simon; Garric, Gilles
Abstract The solution of a 10 year simulation of the Arctic Ocean, produced using a 6 km resolution coupled ocean and sea‐ice model, is analyzed to understand the variability, control, and forcing mechanisms of the volume fluxes through the Canadian Arctic Archipelago (CAA) and Davis Strait (DS). The analysis focuses on variability at monthly time scales. Analysis confirms the "control" of volume fluxes through the CAA, proposed in previous studies, by (1) variations of sea surface height (SSH) in the "upstream" regions and the relationship of this control to alongshore wind in the Beaufort Sea and (2) by SSH in the "downstream" region in Baffin Bay that may be related to wind stress in Baffin Bay and the northern Labrador Sea. The effectiveness of these control and forcing mechanisms vary for fluxes through different sections and for different seasons. Variation of the southward flux through DS is directly influenced by fluxes through Nares Strait (NS) and Barrow Strait (BS) in summer, fall, and winter. In spring, variations of the southward and northward fluxes through DS are closely related to each other and correspond to changes in the SSH along pathways of the Irminger Current, and the East and West Greenland Currents.